Transcatheter heart valve selection in patients with low ejection fraction and aortic stenosis. Issue 12 (15th November 2022) - Mustafa, Ahmad; Kliger, Chad; Pirelli, Luigi; Kodra, Arber; Wang, Denny; Singh, Priyanka; Arnone, Paley; Patel, Apurva; Liu, Shangyi; Mihelis, Efstathia; Koss, Elana; Wilson, Sean; et al.
Abstract: Objective: The aim of this study was to compare outcomes of transcatheter heart valve (THV) choice in patients with left ventricular (LV) systolic dysfunction. Background: The management congestive heart failure with combined LV systolic dysfunction and severe aortic stenosis (AS) is challenging, yet transcatheter aortic valve replacement (TAVR) has emerged as a suitable treatment option in such patients. Head‐to‐head comparisons among the balloon‐expandable (BEV) and self‐expandable (SEV) THV remain limited in this subgroup of patients. Methods: In this retrospective study, we included patients with severe AS with LV systolic dysfunction (LVEF ≤40%) who underwent TAVR at four high volume centers. Two thousand and twenty‐eight consecutive patients were analyzed, of which 335 patients met inclusion criteria. One hundred fourty‐six patients (43%) received a SEV, and 189 patients (57%) received a BEV. Results: Baseline characteristics were similar except for a higher proportion of females in the SEV group. The primary composite endpoint of in‐hospital mortality, moderate or greater paravalvular (PVL), stroke, conversion to open surgery, aortic valve reintervention, and/or need for permanent pacemaker (PPM) was no different among THV choice. There was more PVL in the SEV group, but higher transaortic gradients in the BEV group. Clinical outcomes and quality of life measures were similar up to 1 year follow‐up. Conclusion: The choice of THV in patients with severe AS and systolic dysfunction must be weighed on a case‐by‐case basis.